Factors Influencing Students’ Attitudes towards Technical and Vocational Education and Training(TVET) - Wong Wei Zhi; Atan @ Yaakub, Siti Anisah (Research in Management of Technology and Business, 2021)
TVET or Technical and Vocational Education and Training program has been extensively recognized as among the most important subjects in the educational system. Unfortunately, TVET has been perceived as second class education by public, particularly parents and students. So, the objective for this research is to identify the major factors that influence students’ attitudes towards Technical and Vocational Education and Training and to determine the relationship between factors and students’ attitudes. This study chose TVET students in UTHM as respondents. A cross-sectional study was done using survey questionnaire. A total of 278 questionnaires distributed to targeted respondents using Google form. Out of 278, only 200 sets of the questionnaire have been returned which was about 71.94% rate of return. Tests conducted in this research were Normality, Reliability Test and Spearman Rho’s Correlation Coefficient Statistic. The results showed that there is significant relationship between all studied variables i.e. parent influence, teacher influence, peer influence, grades in school, future career and job potential, socio-economic, and attitudes towards TVET among TVET students in UTHM. The result of this study can be applied in the area of improving public perceptions toward TVET program particular among students and parents.